Digital Samaritans : Rhetorical Delivery and Engagement in the Digital Humanities - Ridolfo, Jim, 1979-; Project Muse. (Ann Arbor : University of Michigan Press, 2015)
Digital Samaritans explores rhetorical delivery and cultural sovereignty in the digital humanities. The exigence for the book is rooted in a practical digital humanities project based on the digitization of manuscripts in diaspora for the Samaritan community, the smallest religious/ethnic group of 770 Samaritans split between Mount Gerizim in the Palestinian Authority and in Holon, Israel. Based on interviews with members of the Samaritan community and archival research, Digital Samaritans explores what some Samaritans want from their diaspora of manuscripts, and how their rhetorical goals and objectives relate to the contemporary existential and rhetorical situation of the Samaritans as a living, breathing people. How does the circulation of Samaritan manuscripts, especially in digital environments, relate to their rhetorical circumstances and future goals and objectives to communicate their unique cultural history and religious identity to their neighbors and the world? Digital Samaritans takes up these questions and more as it presents a case for collaboration and engaged scholarship situated at the intersection of rhetorical studies and the digital humanities.
Introduction to digital Samaritans -- Between the raindrops and two fires: a brief history of the Samaritans and their diaspora of manuscripts -- From parchment to bytes: digital delivery as a rhetorical strategy -- Leveraging textual diaspora: rhetoric and the digital humanities as engaged scholarship -- The Good Samaritan: at the crossroads of rhetoric and the digital humanities.
English.
Description based on print version record.
Keywords: Samaritans -- Historiography; Library materials -- Digitization; Learning and scholarship -- Technological innovations; RELIGION -- General; RELIGION -- Judaism -- General; Documents de bibliotheque -- Numerisation; Savoir et erudition -- Innovations; Samaritains -- Historiographie; Library materials -- Digitization; Learning and scholarship -- Technological innovations; Samaritans -- Historiography; Tsedaka, Benyamim; Tsedaka, Benyamim; Electronic books